DETEKSI DINI MASALAH PERILAKU PSIKOSOSIAL PADA REMAJA DI SEKOLAH MENENGAH ATAS KOTA MAKASSAR - Yusnaeni, Yusnaeni; Sari Wijayaningsih, Kartika (NHM PRESS, 2023)
Psychosocial is the relationship between social conditions and mental or emotional health. The development of a person's personality comes from social experiences throughout his life so it is called psychosocial development. This development has a huge influence on the quality of a person's ego. The conflict that often arises in psychosocial problems is an identity crisis, the factors that cause an identity crisis are problems in the ability to control emotions, problems placing oneself with peers, and not getting the right figure to achieve a good self-identity. This research aims to determine and analyze the picture of early detection of psychosocial behavior problems in adolescents in high school. This research was conducted in October-November 2023. This is quantitative research. The number of samples in this study was 88 respondents using a random sampling method. Based on descriptive tests, the results of the Post Traumatic Distress Syndrome research were 54 respondents (64.4%), Anxiety and Depression, namely 24 respondents (20.3%), Psychotic Disorders were 10 respondents (15.3%). For early detection of psychosocial behavior problems, the school needs to hold meetings regarding guidance and counseling with students to understand more deeply the problems students are experiencing.